Evidenciação do antígeno da hepatite B (HBsAg) em Triatominae Hepatitis B antigen (HBsAg) in wild triatominae in Brazil - Oswaldo Paulo Forattini; S. Otatti; J. A. N. Candeias; J. G. Vieira; M. L. Rácz (Universidade de São Paulo, 1980)
De 3.200 "manchas" provenientes de insetos dos gêneros Triatoma e Panstrogylus, positivas para sangue humano, 12 deram resultados presuntivamente positivos, por imunodifusão, para HBsAg. Deste total, só 7 casos foram confirmados como positivos, por radioimunoensaio, correspondendo todos eles a "manchas" obtidas de ninfas de Triatoma infestans. A total of 3,200 impressions were fixed on filter paper and were identified as containing human blood obtained from blood-sucking arthropods of the Triatoma and Panstrongylus genre. The impressions were then examined for the presence of the hepatitis B antigen (HBsAg). The immunodifusion technique showed that 12 impressions were presumably HBsAg positive, but the radioimmunoassay technique only confirmed 7 positive results. The positive samples were all obtained from Triatoma infestans nymphae.